Religious and Moral Nihilism in Friedrich Nietzsche and the Nigerian Situation - Damian Tersoo Anyam; Terfa Benjamin-Mary Ageba (LAPAI JOURNAL OF NIGERIA HISTORY, 2021)
contrast to her National Pledge where all keep promising to be faithful, loyal, and honest as well as upholding her honour and glory and calling on God to help them in keeping these promises. This presents Nigeria as a religious and morally sound nation. However, there is serious moral decadence in both religious and secular institutions in Nigeria such that Nigeria is numbered one of the most corrupt countries in the world. It has become a situation where almost all Nigerians want to rule or acquire wealth by hook or by crook. Interestingly, Nietzsche in his book, Thus Spoke Zarathustra and other works interprets this moral decadence as the death of God and calls for abandonment of traditional religious morality. He refers to this as the trans-valuation of values, that is, a complete transformation of traditional moral values. He sees the traditional morality as it was taught by Christianity as not only useless but harmful to mankind. Nietzsche calls it, Slave morality. He feels that it is his mission to destroy such morality and replace it with a more positive morality that encourages the growth of man through the development of his best instincts, a morality of power, strength, ambition, struggle, ruthlessness, etc. As God is dead, for him therefore, mankind is now free, for man has now been liberated from slave morality through which God was destroying him. To look into these notions of religious and moral nihilism, from the Latin word nihil meaning nothingness, this work adapted the qualitative research design where data were sourced from books, journals, periodicals, internet and the Holy Bible. The work employed both expository and analytic methods to carry this out. The expository method was employed to establish Nietzsche’s concept of religious and moral nihilism and the analytic method was employed to advance the effects of his position on contemporary Nigerian religious society. The work discussed the meaning of nihilism, Nietzsche’s profile, his religious nihilism such as the death of God and Anti-Christ and moved to his moral nihilism and its implication on contemporary Nigerian religious society. By analyzing moral and religious nihilism, the writers found out that there has been a decline in traditional religious moral values among Nigerians in this contemporary era. The writers thus established that both religious and secular institutions should be re-oriented on the need for morality and also the need for genuine religious practices that can nip the evils of corruption, exploitation, extortion and deceit in the bud.